GOLGA8 increases bulk antisense oligonucleotide uptake and activity in mammalian cells - Moira A. McMahon; Meghdad Rahdar; Swagatam Mukhopadhyay; Huynh-Hoa Bui; Christopher Hart; Sagar Damle; Margo Courtney; Michael W. Baughn; Don W. Cleveland; C. Frank Bennett (Elsevier, 2023)
Antisense oligonucleotides (ASOs) are short synthetic nucleic acids that recognize and bind to complementary RNA to modulate gene expression. It is well established that single-stranded, phosphorothioate-modified ASOs enter cells independent of carrier molecules, primarily via endocytic pathways, but that only a small portion of internalized ASO is released into the cytosol and/or nucleus, rendering the majority of ASO inaccessible to the targeted RNA. Identifying pathways that can increase the available ASO pool is valuable as a research tool and therapeutically. Here, we conducted a functional genomic screen for ASO activity by engineering GFP splice reporter cells and applying genome-wide CRISPR gene activation. The screen can identify factors that enhance ASO splice modulation activity. Characterization of hit genes uncovered GOLGA8, a largely uncharacterized protein, as a novel positive regulator enhancing ASO activity by ∼2-fold. Bulk ASO uptake is 2- to 5-fold higher in GOLGA8-overexpressing cells where GOLGA8 and ASOs are observed in the same intracellular compartments. We find GOLGA8 is highly localized to the trans-Golgi and readily detectable at the plasma membrane. Interestingly, overexpression of GOLGA8 increased activity for both splice modulation and RNase H1-dependent ASOs. Taken together, these results support a novel role for GOLGA8 in productive ASO uptake.